Retorika dalam Pidato Anies Baswedan di Youtube Tahun 2017-2022 - Yuliza Putri; Ernanda Ernanda; Yoga Mestika Putra (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2023)
This study aims to describe the forms of pathos and logos in Anies Baswedan's speech using Aristotle's rhetoric. This research use desciptive qualitative approach. The data in this study are words, phrases or sentences contained in Anies Baswedan's 2017-2022 speeches sourced from Youtube. The data that has been transcribed is then codified, classified, and interpreted to answer the research problem formulation. The results of the study show that there are 81 uses of pathos rhetoric which aim to appeal to the audience's emotions so that feelings of emotion, joy, pride, hope, and enthusiasm arise. The linguistic features found from the form of pathos are parallel sentences (35 data), cohesive sentences (7 data), correlative conjunctions (8 data), contrasting sentences (7 data), figurative language (7 data) metaphors (15 data), connotative sentences (1 data), and denotation sentences (1 data). In the logos form, 30 data were found which aim to convey information about time information, place information, distance information, achievements, work programs that have been implemented, and aim to increase knowledge. From the results of data analysis, this study concluded that Anies Baswedan had high rhetorical abilities. Through the language he uses, Anies Baswedan can influence other people to gain public trust so that he can carry out programs that are his vision and mission in serving as governor of DKI Jakarta for the 2017-2022 period. Â Abstrak Penelitian ini bertujuan untuk mendeskripsikan bentuk-bentuk pathos dan logos dalam pidato Anies Baswedan dengan menggunakan retorika Aristoteles. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data dalam penelitian ini adalah kata, frasa, atau kalimat yang terdapat dalam pidato Anies Baswedan tahun 2017-2022 yang bersumber dari Youtube. Data yang telah ditranskripsi kemudian dikodifikasi, diklasifikasi, dan diinterpretasi untuk menjawab rumusan masalah penelitian. Hasil penelitian menunjukkan bahwa terdapat 81 penggunaan retorika bentuk pathos yang bertujuan untuk menarik emosi audiens sehingga timbul rasa haru, senang, bangga, berharap, dan semangat. Fitur linguistik yang ditemukan dari bentuk pathos yaitu kalimat paralel (35 data), kalimat kohesi (7 data), konjungsi korelatif (8 data), kalimat kontras (7 data), bahasa figuratif (7 data) metafora (15 data), Kalimat konotasi (1 data), dan kalimat denotasi (1 data). Bentuk logos ditemukan 30 data yang bertujuan untuk menyampaikan informasi tentang keterangan waktu, keterangan tempat, keterangan jarak, prestasi, program kerja yang sudah terlaksana, dan bertujuan untuk menambah pengetahuan. Dari hasil analisis data, penelitian ini menyimpulkan bahwa Anies Baswedan memiliki kemampuan retorika yang tinggi. Melalui bahasa yang digunakannya, Anies Baswedan dapat mempengaruhi orang lain untuk memperoleh kepercayaan publik sehingga dapat menjalankan program-program yang menjadi visi misinya dalam menjabat sebagai gubernur DKI Jakarta periode 2017-2022